Medical applications with disentanglements: First MICCAI Workshop, MAD 2022, held in conjunction with MICCAI 2022, Singapore, September 22, 2022 :proceedings - Fragemann, Jana; Li, Jianning; Liu, Xiao; Tsaftaris, Sotirios A.; Egger, Jan; Kleesiek, Jens Philipp (Lecture notes in computer science, 2023)
This book constitutes the post-conference proceedings of the First MICCAI Workshop on Medical Applications with Disentanglements, MAD 2022, held in conjunction with MICCAI 2022, in Singapore, on September22, 2022.The 8 full papers presented in this book together with one short paper were carefully reviewed and cover generative adversarial networks (GAN), variational autoencoders (VAE) and normalizing-flow architectures as well as a wide range of medical applications, like brain age prediction, skull reconstruction and unsupervised pathology disentanglement
Keywords: Konferenzschrift; Pathologie; Medizinische Informatik